IDENTIFIKASI MOLEKULAR ISOLAT KAPANG PENGHASIL Ã-GLUCAN BERDASARKAN DAERAH INTERNAL TRANSCRIBED SPACER (ITS) - Srikandace, Yoice; Caterina A, Ines Irene; Mangunwardoyo, Wibowo (BERITA BIOLOGI, 2009)
Research was conducted to identify the fungal isolate G.23 which produces b-glucan from the Biopharmacy Laboratoriums collection.Indonesian Institute of Sciences (LIP1) based on the sequence of the Internal Transcribed Spacer (ITS) regions.DNA was isolated from mycelia and the ITS region was amplified by Polymerase Chain Reaction (PCR) with ITS1 and ITS4 primers. The PCR product was purified using the QIAquick PCR Purification kit (Qiagen). BigDye terminator cycle sequencing Ready Reaction Kit (Perkin Elmer Applied Biosystem) was used and the product was purified with the AutoSEQ G-50 Kit (Qiagen).The sequence obtained analysed using Basic Local Alignment Search Tool nucleotide (BLAST)n homology search.The BLASTn result showed that the fungal isolate G.23 belongs to the genus Aspergillus. Taxa closely related to this isolate were Aspergillus elegans,A. ochraceus and A.sclerotiorum with 96% sequence homology.ClustalX was used for sequence-alignment. Phylogenetic analysis was constructed using the Neighbour Joining (NJ) method with Kimura two parameters. The phylogenetic tree obtained showed that fungal isolate G.23 separated from A. elegans, A. ochraceus and A. sclerotiorum which indicated that fungal G.23 belonged to a different spesies.Morphological observation on culture and microscopic appearance of the fungal isolate G.23 supported that this isolate differs from A. elegans, A. ochraceus and A. sclerotiorum.